PENGARUH JENIS KELAMIN DAN PENDIDIKAN TERHADAP FAKTOR RISIKO KEJADIAN TUBERKULOSIS PARU DI WILAYAH KERJA PUSKESMAS LASUSUA KABUPATEN KOLAKA UTARA TAHUN 2023 - Haddase, Hasriadi; ruf, Ma’; Zamli, Zamli (Ensiklopedia of Journal, 2024)
Abstract: Tuberculosis is an infectious disease that can cause health problems and is also one of the top 10 causes of death from infectious diseases in the world, Pulmonary tuberculosis is caused by the bacterium Mycobacterium tuberculosis, which means that when people cough, they expel the bacteria into the air. The aim of the study was to determine the analysis of risk factors for pulmonary tuberculosis in the Work Area of the Lasusua Public Health Center, North Kolaka Regency 2023 years. This research was conducted in the working area of the Lasusua Public Health Center, North Kolaka Regency. The type of research used was an analytical survey with a "case control" approach. The number of samples in this study were  60 people (30 cases: 30 controls), using simple random sampling technique and questionnaires as research instruments. The results showed that gender was a risk factor for pulmonary tuberculosis with OR = 3,500 (95% CI 1,201 – 10,196), Education was a risk factor for pulmonary tuberculosis with OR = 6,882 (95% CI 1,707 – 27,752), Residential density was a risk factor for pulmonary tuberculosis with an OR = 3,455 (95% CI 1,195 – 9,990), smoking is a risk factor for pulmonary tuberculosis with an OR = 13,000 (95% CI 3,551 – 47,597), floor type is a risk factor for pulmonary tuberculosis with a value OR = 5,231 (95% CI 1,657 – 16,515), Ventilation is a risk factor for pulmonary tuberculosis with OR = 3,000 (95% CI 1,046 – 8,603). The results of the multivariate analysis of the most dominant variable which is a risk factor is smoking with an Exp(B) or OR value of 42,452.Keywords: Risk Factors, Pulmonary Tuberculosis